Rītikālīna kāvya-vidhāoṃ kā śāstrīya adhyayana : rītikālīna krtiyoṃ ke kośa sahita - Pavana, 1937- (Anupama Prakāśana ; vitaraka Risarca Pablikeśana ina Śosala Sāinseja, 1979)
Study on Hindi stylistic poetry, 1650-1850.